Respuesta :
Answer:
Simplifying
4x + -7 = -2x + -5
Reorder the terms:
-7 + 4x = -2x + -5
Reorder the terms:
-7 + 4x = -5 + -2x
Solving
-7 + 4x = -5 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
-7 + 4x + 2x = -5 + -2x + 2x
Combine like terms: 4x + 2x = 6x
-7 + 6x = -5 + -2x + 2x
Combine like terms: -2x + 2x = 0
-7 + 6x = -5 + 0
-7 + 6x = -5
Add '7' to each side of the equation.
-7 + 7 + 6x = -5 + 7
Combine like terms: -7 + 7 = 0
0 + 6x = -5 + 7
6x = -5 + 7
Combine like terms: -5 + 7 = 2
6x = 2
Divide each side by '6'.
x = 0.3333333333
Simplifying
x = 0.3333333333
Step-by-step explanation:
Answer:
x = - 1
Step-by-step explanation:
Let's solve
4x + 7 = 2x + 5
Subtract 2x from both sides.
4x + 7 −2x = 2x + 5 −2x
2x + 7 = 5
Subtract 7 from both sides.
2x + 7 − 7 = 5 −7
2x = −2
Divide both sides by 2.
2x / 2 = −2 / 2
x = −1